The new power elite : inequality, politics and greed - Shipman, Alan (Book Network Int'l Limited trading as NBN International (NBNi) : Anthem Press, 2018)
'Greedy Elites' explains why today's revolt against the 'rich and powerful' is led by billionaires and political insiders, sidelining elites' traditional enemies. It links social, economic and political theory and evidence to show how rivalries within an elite always eclipse (and co-opt) popular or class-based rebellions in driving social change.
Keywords: Elite (Social sciences) -- United States.; Wealth -- Political aspects -- United States.; Power (Social sciences) -- United States.; Rich people -- United States.; Élite (Sciences sociales) -- États-Unis.; Richesse -- Aspect politique -- États-Unis.; Pouvoir (Sciences sociales) -- États-Unis.; Riches -- États-Unis.; POLITICAL SCIENCE -- Political Economy.; Elite (Social sciences); Power (Social sciences); Rich people; United States